Entre rastros e restos: a imaginação como arqueologia da imagem - Ciquini, Fabio Henrique (2016)
The main objective of this research is to examine whether imagination can be configured as an “archaeological tool” over the image in its saturated media environments. The work begins considering Google Street View as its media environment and we affirm that inflation and continuous dissemination of images by its apparatuses causes a anaestheticization of senses. The selected corpus of analysis was the photographic act of German photographer Michael Wolf in the series titled Street View, in which author takes photos, through computer screen, from Google Street View site. By this object, one analyzes the inventive and delved character of this photographic dynamic over the images, which one suggests an archaeological nature in this photographic act. By this point, the idea of an archeology of image is here evoked in the sense of depth perception, which points not only to past traces hidden in the depths of the image, but also prospect signal elements that indicate future tracks in it. Therefore, one justifies the need for this archaeological sight, as a way to overcome the celebrated superficial visuality in mediatic images, and our suggested hypothesis is that the archaeological tool, which is able to delve on the image is imagination. Consequently, imagination would operate as a point of equalization in front of saturated visual media environments. The methodology adopted was an approximation to the object, which took place oblique cuts and a broader target, one considers for an Archeogenealogy of concepts and theories. The research approaches aspects of Image Theory in Walter Benjamin, Aby Warburg, Hans Belting and Norval Baitello Jr., about media environments and how images in excess dulls perception, there was discussion with reflections of Theory of Media in authors like Vilém Flusser – concepts of reign of garbage and escalating of abstraction - Dietmar Kamper (imaginary orbit and force of imagination) and Malena Contrera, concept of mediasphere. Regarding the concept of imagination, one argues based on Bachelard, and about visual thinking we consider reflections from Arnheim and Damasio. As a result, therefore, we emphasize how imagination is configured as an archeology of image based on three aspects: thought by images, optical unconscious and distraction. Thereby, one reaffirms the fundamental role of the imagination, and thus the body, in its anthropological relationship with images